Experimental investigation of mechanical properties of concrete mix with lightweight expanded polystyrene and steel fibers - Shah, Syed Jahanzaib; Naeem, Asad; Hejazi, Farzad; Ahmed Mahar, Waqas; Haseeb, Abdul (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The demand for lightweight aggregates in concrete compositions for diverse structural and non-structural applications in contemporary building construction has increased. This is to achieve a controllable low-density lightweight concrete, which reduces the overall structural weight. However, the challenge lies in achieving an appropriate strength in lightweight concrete while maintaining a lower unit weight. This research aims to evaluate the performance of lightweight concrete by integrating expanded polystyrene (EPS) as a partial replacement for coarse aggregate. Test specimens were cast by blending EPS with coarse aggregate at varying proportions of 0%, 15%, 30%, and 45%, while maintaining a constant water-to-binder ratio of 0.60. To enhance the bonding and structural capabilities of the proposed lightweight concrete mixes, reinforcement with 2% and 4% steel fibers by volume of the total concrete mix was incorporated. Silica fume was introduced into the mix to counteract the water hydrophobicity of EPS material and enhance the durability of lightweight concrete, added at a rate of 10% by weight of cement in all specimens. A total of 60 samples, including cylinders and beams, were prepared and cured over 28 days. The physical and mechanical properties of the lightweight EPS-based concrete were systematically examined through experimental testing and compared against a standard concrete mix. The analysis of the results indicates that EPS-based concrete exhibits a controllable low density. It also reveals that incorporating reinforcement materials, such as steel fibers, enhances the overall strength of lightweight concrete. © 2024 by the authors.